The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1002/ppul.20055
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled fluticasone dipropionate decreases levels of nitric oxide in recurrenty wheezy infants

Abstract: We examined the effect of inhaled fluticasone diproprionate (FDP) on symptoms, lung function (FEV(0.5)), and exhaled nitric oxide (Fe(NO)) in infants with recurrent wheeze and raised Fe(NO). Thirty-one infants aged 6-19 months (mean, 12.7 months; 12 girls) completed the study. All infants had a history of recurrent wheeze and a parental history of atopy. All children had raised Fe(NO), as determined by an offline tidal breathing technique prior to randomization. Lung function and Fe(NO) were assessed before an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 29 publications
2
39
0
1
Order By: Relevance
“…12,44 In fact, the FDA approved the use of FeNO in individuals with asthma to monitor response to anti-inflammatory agents. 44 The results of the present study confirm that FeNO may be a valuable biomarker of response to inhaled anti-inflammatory therapy in children with asthma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,44 In fact, the FDA approved the use of FeNO in individuals with asthma to monitor response to anti-inflammatory agents. 44 The results of the present study confirm that FeNO may be a valuable biomarker of response to inhaled anti-inflammatory therapy in children with asthma.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13] In a recent randomized trial, Smith et al found that maintenance doses of inhaled corticosteroid could be significantly reduced by using FeNO to guide treatment in chronic asthma in adults. 14 Thus, FeNO, is increasingly recognized as a supplementary tool to optimize pharmacologic therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced lung function in infancy was associated with respiratory morbidity and treatment needs at preschool age [65]. Some studies showed improvement of lung function, such as forced expiratory volume in 0.5 s, in infants with recurrent wheezing after ICS treatment or oral treatment with montelukast, whereas others did not show significant changes [63,64,74,75].…”
Section: Infant Lung Functionmentioning
confidence: 99%
“…Different methods have been used to assess lung function in wheezy infants including the analysis of tidal flow-volume breathing loops, forced expirations from either normal inspiration (rapid thoracic compression technique) or from total lung capacity (raised volume rapid thoracic compression technique) or body plethysmography [62][63][64][65][66][67]. Infant lung function testing has been used to assess phenotypes in infants with wheezing and to develop prediction models for persistent asthma [68].…”
Section: Infant Lung Functionmentioning
confidence: 99%
“…Exhaled nitric oxide and other assessments of airways inflammation Elevated exhaled nitric oxide fractions (FeNO) have been found in wheezing infants, especially when they are atopic [70,71], and these normalise during treatment with ICSs [72] and montelukast [73,74]. FeNO in infants are affected by environmental exposures and genetic predisposition to atopy [75].…”
Section: Lung Function Testsmentioning
confidence: 99%